Financial Ratios and Stock Return in the Food and Beverage Company - Dwijayani, Henny; Marzuki, Moh Idris; Sari, Linda Ratna; Muchtar; Aslichah (EkBis: Jurnal Ekonomi dan Bisnis, 2023)
This study uses financial ratio analysis to investigate the company's stock returns. This study aims to determine the dominant influence of several financial ratios on stock returns. Financial ratios are helpful in evaluating relied returns. The quantitative research approach is used to analyze how financial ratios affect stock returns. The population of this study is companies in the food and beverage sector listed on the Indonesia Stock Exchange. The analysis was carried out from 2017 to 2020 using secondary data sources. Purposive sampling is used in this study, with the sample chosen based on predetermined standards and subjected to multiple linear regression analysis. The analysis' findings demonstrate that DER and TATO have no significant effect on stock returns, while CR, ROA, and ROE have a significant effect on stock returns. optimal corporate profitability is not always achieved by having too many current assets. Additionally, unproductive management of surplus and unused funds will impact declining stock returns. The results of this study indicate that idle current assets cannot generate company profitability because the current ratio is too high indicating an excess of current assets relative to fixed assets.